Multimodal Language Stimulation: Integrating Digital Media into Early Childhood Morning Meeting Routines - Indah Tri Hizriyah; Aip Syarifudin; Abdul Muiz Rouf (International Journal of Educational Qualitative Quantitative Research, 2026)
Early childhood language development requires active dialogic interaction; however, conventional morning meeting routines frequently default to passive, teacher-centered monologues. While digital media provides robust multimodal stimulation, it is rarely integrated directly into face-to-face collaborative routines to overcome expressive language constraints. This study investigates how the systematic integration of interactive digital media into morning meeting routines scaffolds both the receptive and expressive language capacities of young learners. Employing a cyclical practitioner-led action research design, the study involved 17 young learners aged between 5 and 6 years who initially exhibited severe communicative passivity. The intervention utilized interactive presentations, digital word cards, and audiovisual storytelling across two complete instructional cycles. Data were gathered through behavioral observation, dialogue transcription, and performance rubrics validated via inter-rater reliability protocols. Quantitative analysis revealed a significant acceleration in overall language mastery, escalating from a pre-intervention baseline of 41% to an optimal 86.2% by the conclusion of the second cycle. Furthermore, qualitative micro-analysis demonstrated that synchronized visual and auditory cues successfully reduced extraneous cognitive load. This cognitive optimization enabled the children to transition from silent peer mimicry to autonomous sentence construction and coherent narrative expression. By bridging the Cognitive Theory of Multimedia Learning with sociocultural scaffolding principles, this research establishes that digital tools can function as collaborative social glue rather than isolating devices. Ultimately, this instructional framework provides a cost-effective and scalable blueprint for international educators seeking to optimize child-centered communicative agency in resource-constrained environments.